Un proceso de reorganización territorial advertido desde las escuelas elementales: el valle de Toluca entre fines del siglo XVIII y principios del siglo XIX José Bustamante Vismara (Tzintzun, Revista de Estudios Históricos, 2016)
his paper discusses the process of territorial reorganization which took placein the Toluca Valley between the end of the 18th and the beginning ofthe 19th century, based on the study of elementary schools. he study aimsto shed light on the administration and the resource management of theseinstitutions in two contrasting eras: on the one hand, what happened in theperiods of viceroyalty and independence, and on the other hand, the eventsthat occurred in the jurisdictions of which the city of Toluca was a part (irstthe marquis period and followed by the state period). his was contrast comparedto other towns in the valley. he documentary sources which have servedas background support to this study come from national archives, as wellas from a dozen of municipal historical archives which keep a rich heritage ofthe period in question. As a corollary, we suggest variations and continuities,among them processes of territorial reorganization.
Keywords: schools; administration; finances; Toluca Valley; territory